2004
DOI: 10.1093/humrep/deh528
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic spindle morphogenesis in in vivo and in vitro matured mouse oocytes: insights into the relationship between nuclear and cytoplasmic quality

Abstract: The results emphasize the importance of coupling MT remodeling and cell cycle components during oocyte maturation to achieve a balanced coordination of nuclear and cytoplasmic maturation that under physiological conditions occurs within the first 5 h of LH stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
69
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 39 publications
11
69
0
Order By: Relevance
“…Recently we have shown that the temporal progression of cytoplasmic and nuclear remodeling events were distinctly different in in vivo matured oocytes compared with oocytes matured under basal in vitro conditions in the outbred CF-1 mouse strain (Sanfins et al 2003(Sanfins et al , 2004, further supporting the notion that in vivo produced ova are generally of superior quality with respect to production of healthy embryos and offspring. It is well established that during in vitro maturation, although nuclear maturation takes place, complete cytoplasmic maturation is not assured (Eppig et al 1996).…”
Section: Introductionmentioning
confidence: 59%
“…Recently we have shown that the temporal progression of cytoplasmic and nuclear remodeling events were distinctly different in in vivo matured oocytes compared with oocytes matured under basal in vitro conditions in the outbred CF-1 mouse strain (Sanfins et al 2003(Sanfins et al , 2004, further supporting the notion that in vivo produced ova are generally of superior quality with respect to production of healthy embryos and offspring. It is well established that during in vitro maturation, although nuclear maturation takes place, complete cytoplasmic maturation is not assured (Eppig et al 1996).…”
Section: Introductionmentioning
confidence: 59%
“…Maintaining a structural interaction during the earliest stages of meiotic resumption between the GV and oocyte cortex is likely to impact spindle morphogenesis at later stages of meiotic maturation as well as over-all developmental competence of the egg. In vivo matured oocytes assemble spindles within a contracted nuclear matrix comprised of lamin B that was proposed to limit MT assembly and MTOC involvement thus yielding diminutive spindles [39] compared to their in vitro matured counter. The notion of conserving resources at the protein level has also been studied in relation to spindle and/or polar body size.…”
Section: Discussionmentioning
confidence: 99%
“…COCs were cultured under conditions that either promote cumulus expansion, by adding hormone supplementation as well as the addition of FBS (IVM+), or not (IVMb) [8,39]. In IVMb (basal conditions, n=30), oocytes undergo GVBD within 2 h and chromosome condensation proceeds within a centrally positioned GV (Fig.…”
Section: Relationship Between Tzp Patterning and Spindle Position Durmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro, oocytes begin their maturation earlier than in vivo (Motlik & Fulka, 1976) which is most probably a consequence of their premature extraction from the ovaries (Sanfins et al, 2004). Ovarian follicles contain inhibiting factors that retain the oocyte at proper meiotic phase for adequate time.…”
Section: Ivm Methodsmentioning
confidence: 99%